Effects of N-functional groups on the electron transfer kinetics of VO2+/VO2+ at carbon: Decoupling morphology from chemical effects using model systems - Perova, Tatiana; Colavita, Paula; Costa de Oliveira, Maida (My University, 2024)
Carbons and nanocarbons are important electrode materials for vanadium redox flow battery applications, however, the kinetics of vanadium species are often sluggish at these surfaces, thus prompting interest in functionalization strategies to improve performance. Herein, we investigate the effect of N-functionalities on the VO2+/VO2 + redox process at carbon electrodes. We fabricate thin film carbon disk electrodes that are metal-free, possess well-defined geometry and display smooth topography, while featuring different N-site distribution, thus enabling a mechanistic investigation of the intrinsic surface activity towards VO2+/VO2 +. Voltammetry and electrochemical impedance spectroscopy show that N-functionalities improve performance, with pyridinic/ pyrrolic-N imparting the most significant improvements in charge transfer rates and reversibility, compared to graphitic-N. This was further supported by voltammetry studies on nitrogen-free electrodes modified via aryl diazonium chemistry with molecular pyridyl adlayers. Computational modeling using an electrochemical chemical mechanism indicates that introduction of surface pyridinic/pyrrolic-N can increase the heteroge neous rate constants by approximately two orders of magnitude relative to those observed at nitrogen-free carbon (k0 = 1.29 × 10− 4 vs 9.34 × 10− 7 cm/s). Simulations also suggest that these N-functionalities play a role in affecting reaction rates in the chemical step. Our results indicate that nitrogen incorporation via basic functional groups offers an interesting route to the design of advanced carbon electrodes for VRFB devices.
PUBLISHED
Keywords: Electrocatalysis; Finite element simulations; Heterogeneous charge transfer; Aryldiazonium; Pervanadyl; Vanadyl; Vanadium; Nanoscience & Materials; Materials, Physical Properties